2021
DOI: 10.3389/fphys.2021.740666
|View full text |Cite
|
Sign up to set email alerts
|

EH Domain-Containing 2 Deficiency Restricts Adipose Tissue Expansion and Impairs Lipolysis in Primary Inguinal Adipocytes

Abstract: Lipid uptake can be facilitated via caveolae, specific plasma membrane invaginations abundantly expressed in adipocytes. The dynamin-related protein EH domain-containing 2 (EHD2) stabilizes caveolae at the cell surface. Here, we have examined the importance of EHD2 for lipid handling using primary adipocytes isolated from EHD2 knockout (Ehd2−/−) C57BL6/N mice. Following high-fat diet (HFD) feeding, we found a clear impairment of epididymal, but not inguinal, adipose tissue expansion in Ehd2−/− compared with Eh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Thus, we have provided more evidence that LPL hypermethylation can predispose to metabolic diseases like T2D. Similarly, EHD2, the EH domain-containing 2, is a known obesity-associated gene implicated in GLUT4 endocytosis and in the maintenance of intracellular lipid metabolism in adipocytes [46,47]. Its methylation has only been found as altered in epididymal adipocytes of mice with obesity [48].…”
Section: Discussionmentioning
confidence: 83%
“…Thus, we have provided more evidence that LPL hypermethylation can predispose to metabolic diseases like T2D. Similarly, EHD2, the EH domain-containing 2, is a known obesity-associated gene implicated in GLUT4 endocytosis and in the maintenance of intracellular lipid metabolism in adipocytes [46,47]. Its methylation has only been found as altered in epididymal adipocytes of mice with obesity [48].…”
Section: Discussionmentioning
confidence: 83%
“…In recent studies, we and others have confirmed a role for EHD2 in lipid handling using a global EHD2 knockout (EHD2 KO) C57Bl6/N mouse model, which displayed altered lipid metabolism ( Matthaeus et al. , 2020 ; Fryklund et al. , 2021 ), impaired lipolysis, and diminished insulin-mediated inhibition of lipolysis in primary adipocytes ( Fryklund et al.…”
Section: Introductionmentioning
confidence: 90%
“…, 2020 ; Fryklund et al. , 2021 ), impaired lipolysis, and diminished insulin-mediated inhibition of lipolysis in primary adipocytes ( Fryklund et al. , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the overexpression of EHD2 in human adipocytes increases lipid signaling and inhibits the activity of the transcription factor PPARγ 61 . Meanwhile, Fryklund et al 62 revealed that the deficiency of EHD2 inhibits the expansion of adipose tissue and impairs lipolysis in primary inguinal adipocytes. They also highlighted the variations in lipid metabolism controlled by EHD2 in different adipose tissue depots.…”
Section: The Role Of Ehd2 In Lipid Uptake and Metabolismmentioning
confidence: 99%